1995
DOI: 10.1128/aac.39.11.2528
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of short-course therapy (5 days) with cefuroxime axetil in treatment of secondary bacterial infections of acute bronchitis

Abstract: Five hundred thirty-seven patients were enrolled in two independent, investigator-blinded, multicenter, randomized clinical trials comparing the clinical and bacteriologic efficacies and the safety of 5-or 10-day treatment with cefuroxime axetil with those of 10-day treatment with amoxicillin-clavulanate in the treatment of secondary bacterial infections of acute bronchitis. Patients received either 5 or 10 days of treatment (n ‫؍‬ 177 in each group) with cefuroxime axetil at 250 mg twice daily or 10 days of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The frequency of occurrence of S. aureus appeared to be particularly high in this study, but this may have been related to the criteria used to determine the acceptability of sputum samples. Although the proportion of infections caused by S. pneumoniae was relatively low, the incidence of recovery of this organism varies from year to year, and rates of pneumococcal infection similar to those found in the present study have been observed in other studies (17,24). In addition, recovery of S. pneumoniae from transported clinical samples is relatively difficult.…”
Section: Resultssupporting
confidence: 74%
“…The frequency of occurrence of S. aureus appeared to be particularly high in this study, but this may have been related to the criteria used to determine the acceptability of sputum samples. Although the proportion of infections caused by S. pneumoniae was relatively low, the incidence of recovery of this organism varies from year to year, and rates of pneumococcal infection similar to those found in the present study have been observed in other studies (17,24). In addition, recovery of S. pneumoniae from transported clinical samples is relatively difficult.…”
Section: Resultssupporting
confidence: 74%
“…Macfarlane et al identified viruses in only 19% of patients, while typical and atypical bacteria were identified in 25.9% and 23.7% of patients, respectively [7]. In other studies, bacteria were detected in sputum samples in 45% of acute bronchitis patients [8,9]. In addition, several authors suggested that some patients with acute bronchitis had mixed infections involving both viruses and bacteria.…”
Section: Resultsmentioning
confidence: 97%
“…Cefuroxime axetil is the subgroup of b-lactams named as cephalosporin [35]. But the cytosolic carbonic anhydrase isozymes were given more inhibition effects than tumor associated isozymes of hCA IX and hCA II with their IC 50 values (hCA I; 2.92 £ 10 25 mM, hCA II; 2.12 £ 10 25 mM).…”
Section: Resultsmentioning
confidence: 99%